PENGARUH PELAYANAN ADMINISTRASI DAN KINERJA PEGAWAI TERHADAP KEPUASAN MASYARAKAT PADA KANTOR DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN SORONG - Susetyowati Sofia; Johny Paembonan; Digor Mufti (KALIANDA HALOK GAGAS, 2022)
This study aims to determine (1) the effect of administrative services on community satisfaction at the Sorong Regency Population and Civil Registration Office. (2) The Effect of Employee Performance on Community Satisfaction at the Sorong Regency Population and Civil Registration Office. (3) The Effect of Administrative Services and Employee Performance on Community Satisfaction at the Sorong Regency Population and Civil Registration Office. This study uses descriptive and correlation methods using a quantitative approach. The population in this study was the people of Sorong Regency, which amounted to 101 people. The data collection technique in this study used a probability sampling technique with the Slovin formula. The sample in this study amounted to 81 people. The results showed that (1) Administrative Services on Community Satisfaction at the Sorong Regency Population and Civil Registration Office obtained a significant value of 0.000 which was smaller than the 0.05